2009
DOI: 10.1021/om9007373
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)-Catalyzed [2+2], [2+2+2], and [2+2+2+2] Cycloadditions of Dienes or Alkynes with a Bis-ene

Abstract: A novel metal-catalyzed, all-alkene [2þ2þ2] cycloaddition reaction involving a strained and conformationally restricted bis-ene and a diene is reported. 1 Modification of the catalyst leads to competition with a diene-ene [2þ2] reaction, and when an alkyne is used in place of the diene, [2þ2þ2] and [2þ2þ2þ2] reactions occur involving the bis-ene and 1 or 2 equiv of the alkyne, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…One of the few examples of utilising Rh(I)-arene complexes for cycloaddition reactions was provided by Wender et al 68 They used [Rh(COD)(naphthalene)]SbF 6 for the coupling of dienes or alkynes with alkene compounds in [2+2], [2+2+2] and [2+2+2+2] cycloadditions. It was found that the carbon monoxide can play an important role in switching the reaction between the different reaction types.…”
Section: Rhodium(i)-complexes As Catalystsmentioning
confidence: 99%
“…One of the few examples of utilising Rh(I)-arene complexes for cycloaddition reactions was provided by Wender et al 68 They used [Rh(COD)(naphthalene)]SbF 6 for the coupling of dienes or alkynes with alkene compounds in [2+2], [2+2+2] and [2+2+2+2] cycloadditions. It was found that the carbon monoxide can play an important role in switching the reaction between the different reaction types.…”
Section: Rhodium(i)-complexes As Catalystsmentioning
confidence: 99%
“…Recently, Wender and co-workers reported the Rh-catalyzed [2+2+2] cycloaddition of 25 with dienes to afford the corresponding tetracyclic products 147 (Scheme 35) [42]. These authors proposed a mechanism involving oxidative cyclization of 25 to afford a metallotetracyclic intermediate 148.…”
Section: Metal-catalyzed/mediated Reactions Of Cyclooctatetraene Valementioning
confidence: 99%
“…To rapidly implement molecular complexity from readily available simple starting materials, transition metal-catalyzed carbocyclization and cycloaddition reactions are recognized as synthetically very important processes. Considerable advances have been made recently in the development of higher order cycloaddition reactions such as [2+2+2+1], [3+3+1], [2+2+2+2], [4+2+2], [5+2+1], and [5+1+2+1] processes. Various polycyclization reactions have been employed for the construction of natural and unnatural fused-ring systems that can be further elaborated into specific targets.…”
Section: Introductionmentioning
confidence: 99%